Upaya Peningkatan Karakter Kreatif Melalui Media Poserlok Di Kelas XC SMAN 5 Kota Madiun - Sunarno, Sunarno; Hartono, Yudi; Nurkholifah, Siti (LPPM Universitas Putera Batam, 2024)
Creative is one of the dimensions in the profile of Pancasila students. Students who are creative are able to adapt and create something different, meaningful, useful, and have a positive impact. The creative dimension has key elements, namely producing original ideas, producing original works and actions, and having the flexibility of thinking in finding alternative solutions to problems. This study aims to improve students' creative thinking skills to get to know the history or local culture in their area. Posters are generally used to attract the attention of readers of information that is to be conveyed. This study applies the Problem Based Learning learning model. This research is a Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of the stages of planning, observation, implementation of actions, analysis, and reflection. Data collection techniques used include observation, interviews, and documentation studies. The results of the study indicate that the application of the Problem Based Learning learning model based on local cultural heritage in history subjects in class XC SMAN 5 Kota Madiun is able to improve students' creative thinking skills. The percentage obtained by students with creative thinking skills in the pre-cycle has been obtained that the increase from the pre-cycle obtained 6 (16.6%) students in the very creative category, in cycle I there was an increase to 15 (41.6%) students in the very creative category, and in cycle II there was also an increase to 29 (80.5%) students in the very creative category